"Konversacionalizmi" i ligjërimit femëror në politikën shqiptare - Hima, Anila (Seminari Ndërkombëtar për Gjuhën, Letërsinë dhe Kulturën Shqiptare, 2017)
The tendency of conversationalization in the public discourse is known as shifting boundaries between written and spoken discourse practices, shifting the public discourse towards a more conversational, informal and spontaneous style to create the impression of a casual conversation with the public. Analyzing a wide range of political speeches held in three discourse contexts - when politicians are in power, in opposition and in the personal context - this paper investigates the phenomenon of conversationalization in the discourse of Albanian female politicians. Using a qualitative and comparative analysis, we aim to examine the form, the context and the purpose of conversationalization in the political discourse of the female politicians. The results are that the tendency towards a conversational and sometimes rather casual discourse is documented on the morphological, syntactic, lexical and phonetic levels; secondly, it is not expressed constantly and consistently in the political discourse analyzed, but prevails in the speeches held by female politicians in the context of the opposition; and thirdly, its purpose is as much public understanding as possible, to gain more popularity in order to secure public understanding, sympathy and support.